THE ROLE OF THE LANGUAGE LABORATORY IN LEARNING ENGLISH AS A SECOND LANGUAGE IN A UNIVERSITY CONTEXT WITH REFERENCE TO SRI LANKA - Chandradasa, Shavindra; Jayawardane, Dimuthu (PEOPLE: International Journal of Social Sciences, 2018)
As per Sri Lankan university students, English is not just a language but also a cultural component. Most of the time it seems difficult to divert these passive learners into active and energetic language learners. Hence, the language laboratory in the Faculty of Science, University of Ruhuna was decided to incorporate into language learning as a new mechanism. In order to analyze the role of the language laboratory in learning English, closed ended questionnaires were distributed among 150 Science students. 30 students plus all the teachers who worked at the faculty of Science were also interviewed. Data was analyzed both qualitatively and quantitatively. The findings revealed that the laboratory was a great motive. Students started attending lecturers. It provided them relaxation, exposure to authentic language, confidence, individuality, interactions, and immediate feedbacks. It was the best place to practice listening and speaking. Nevertheless, the laboratory was not successful in practicing reading and writing than the traditional classroom. In fact, it was neither a problem related to the laboratory nor a matter with the students. It was a problem with the teachers, who failed to implement creative lesson materials. Teachers’ creativity, up to date knowledge, and selection of software will decide the attainment. Language laboratory is not a substitution for a teacher. Traditional classroom is not a dull place either that we should forget. Therefore, a well-adjusted approach will make the language laboratory a perfect strategy in the long-term success of the language learning process.